Tampilan Perilaku Anti Sosial Pada Siswa Sekolah Dasar - Elsa Gustia (IICET (Indonesian Institute for Counseling, Education and Therapy), 2017)
Anti-social behavior is a negative behavior or behavior deviating from the norms, whether the rules of family, school, and society. Types of anti-social behavior in one of them is aggressive behavior, negativism and behavior control. People who have anti-social behavior usually prefer to be alone rather than gathering with the crowd. Risk factors that cause anti-social behavior in a person can be categorized as personal factors, family, as well as related to school and sosial.Upaya child and anti-social handling can be done with the efforts of parents apply authoritative parenting. While the teacher can be attempted to handle anti-social children by applying cooperative learning methods as well as providing psychological attention and the development of multiple intelligence of children.Anti-social behavior is a negative behavior or behavior deviating from the norms, whether the rules of family, school, and society. Types of anti-social behavior in one of them is aggressive behavior, negativism and behavior control. People who have anti-social behavior usually prefer to be alone rather than gathering with the crowd. Risk factors that cause anti-social behavior in a person can be categorized as personal factors, family, as well as related to school and sosial.Upaya child and anti-social handling can be done with the efforts of parents apply authoritative parenting. While the teacher can be attempted to handle anti-social children by applying cooperative learning methods as well as providing psychological attention and the development of multiple intelligence of children.